NMR analysis on the sialic acid‐binding mechanism of an R‐type lectin mutant by natural evolution‐mimicry. Issue 12 (26th May 2016) - Hemmi, Hikaru; Kuno, Atsushi; Unno, Sachiko; Hirabayashi, Jun
Abstract : A sialic acid‐binding lectin (SRC) was created from the C‐terminal domain of an R‐type N ‐acetyl lactosamine‐binding lectin (EW29Ch) by natural evolution‐mimicry. Here, we clarified its sialic acid‐binding mechanism using NMR spectroscopy. The NMR analysis showed differences between conformations of the 6′‐sialyllactose‐bound SRC in the solution state and that in the crystal state, and differences between the internal motion of the loop region in subdomain γ in SRC and that of the corresponding region in EW29Ch. The NMR analysis thus provided useful information to explain the manner of binding to 6′‐sialyllactose in solution, which the previous X‐ray crystal structure analysis lacked. Abstract : Some residues showed two amide resonances only in the 6′‐sialyllactose‐bound state. The interaction of SRC with 6′SiaLac in solution differed from that in crystal state. The internal motion of the extended loop in subdomain γ had higher internal mobility. The internal motion of the flexible loop remarkably changed from that of EW29Ch.